Genome-wide genetic and epigenetic analyses of pancreatic acinar cell carcinomas reveal aberrations in genome stability - Cornelia Jäkel (Nature Portfolio, 2017)
Pancreatic acinar cell carcinoma (ACC) is an aggressive exocrine tumor with largely unknown biology. Here, the authors perform genome- and epigenome-wide analyses from normal and ACC pancreatic tissue that identify aberrations in genome stability and cell cycle control.